Malaysian validation of a sociopolitical control scale for youth - Christens, Brian D.; Krauss, Steven Eric; Zeldin, Shepherd (John Wiley & Sons, 2016)
Empowerment is a process by which people and groups gain control over their lives and environments. The emotional component of psychological empowerment has been assessed using a measure of sociopolitical control. Prior research has measured sociopolitical control as a construct with two dimensions: (a) leadership competence and (b) policy control. This study tested the factor structure of the Sociopolitical Control Scale for Youth (SPCS‐Y) in a sample of Malaysian secondary school students (n = 364; mean age = 16) involved in 3 afterschool programs. Analyses found support for the bidimensional factor structure by using factor loadings and modification indices to reduce the scale from 17 to 8 items. Participants with higher scores on both dimensions of the SPCS‐Y were found to have higher levels of psychological sense of community, school connectedness, and perceived agency. These findings provide support for a measure of youth empowerment in Malaysia and build on recent findings from other nations.